1982
DOI: 10.1007/bf00121670
|View full text |Cite
|
Sign up to set email alerts
|

Stability dependence of fluxes and bulk transfer coefficients in a tropical boundary layer

Abstract: Turbulence data obtained abo+rd a NOAA P-3 research aircraft during flights over the eastern equatorial Pacific Ocean are used to obtain mean vertical profiles of water vapor density, potential temperature, wind speed and fluxes of latent heat, buoyancy and momentum. The variation of eddy fluxes and bulk transfer coefficients as a function of atmospheric stability are plotted for two of the flights. The observed transfer coefficients generally agree with those obtained from parameterizations based on surfacela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 5 publications
1
6
0
1
Order By: Relevance
“…They found that bulk transfer coefficients increased with decreasing wind speed below about 4 m s -•. Similar results were obtained by Greenhut [ 1982] for the latent heat bulk transfer coefficient and the drag coefficient using data from aircraft flights over the equatorial eastern Pacific. Bradley Turbulence data were obtained using the Environmental Research Laboratory/National Oceanic and Atmospheric Administration gust probe system mounted on a WP-3D research aircraft [Greenhut and Gilmer, 1985].…”
Section: Introductionsupporting
confidence: 72%
“…They found that bulk transfer coefficients increased with decreasing wind speed below about 4 m s -•. Similar results were obtained by Greenhut [ 1982] for the latent heat bulk transfer coefficient and the drag coefficient using data from aircraft flights over the equatorial eastern Pacific. Bradley Turbulence data were obtained using the Environmental Research Laboratory/National Oceanic and Atmospheric Administration gust probe system mounted on a WP-3D research aircraft [Greenhut and Gilmer, 1985].…”
Section: Introductionsupporting
confidence: 72%
“…However, large variations in the values of CD were observed for the different data sets and this led to less reliable summarized data. Greenhut (1982) analyzed aircraft data for two separate regions over the eastern equatorial Pacific Ocean; he concluded that fairly good agreement with the theoretical prediction is found from CE data but too large a dependency for C, data on the unstable side. Hicks (1972) using Lake Michigan data found that the data coefficient decreased as stability increased.…”
Section: Bulk Transfer Coefficients As a Function Of The Stability Pamentioning
confidence: 94%
“…It was demonstrated in a number of field campaigns, including the Joint Air-Sea Interaction experiment (JASIN) in the North Sea in the summer of 1978 (e.g., Guymer et al 1983), the Equatorial Pacific Ocean Climate Studies (EPOCS) in the eastern equatorial Pacific in the winter of 1980 (e.g., Greenhut 1982), and the Frontal Air-Sea Interaction Experiment (FASINEX; e.g., Friehe et al 1991). The results show coupling mainly within the atmospheric boundary layer.…”
Section: Introductionmentioning
confidence: 99%